Chemopreventive effects of a Tamarindus indica fruit extract against colon carcinogenesis depends on the dietary cholesterol levels in hamsters - Martinello, Flavia; Kannen, Vinicius; Franco, Joao Jose; Gasparotto, Bianca; Sakita, Juliana Yumi; Sugohara, Atushi [UNESP]; Garcia, Sergio Britto; Uyemura, Sergio Akira (Elsevier B.V., 2017)
Tamarind has significant antioxidant potential. We showed that tamarind protects hypercholesterolemic hamsters from atherosclerosis. Hypercholesterolemia might increase the risk of colon cancer. We investigated whether tamarind extract modulates the risk of colon cancer in hypercholesterolemic hamsters. Hamsters (n = 64) were given tamarind and a hypercholesterolemic diet for 8 weeks. The groups were the control, tamarind treatment, hypercholesterolemic, and hypercholesterolemic treated with tamarind groups. Half of each group was exposed to the carcinogen dimethylhydrazine (DMH) at the 8th week. All hamsters were euthanatized at the 10th week. In carcinogen-exposed hypercholesterolemic hamsters, tamarind did not alter the cholesterol or triglyceride serum levels, but it reduced biomarkers of liver damage (alanine transaminase [ALT], and aspartate aminotransferase [AST]). Tamarind decreased DNA damage in hepatocytes, as demonstrated by analysis with an anti-gamma H2A.X antibody. In liver and serum samples, we found that this fruit extract reduced lipid peroxidation (thiobarbituric acid reactive substances [TBARS]) and increased endogenous antioxidant mechanisms (glutathione peroxidase [GPx] and superoxide dismutase [SOD]). However, tamarind did not alter either lipid per oxidation or antioxidant defenses in the colon, which contrasts with DMH exposure. Moreover, tamarind significantly increased the stool content of cholesterol. Although tamarind reduced the risk of colon cancer in hypercholesterolemic hamsters that were carcinogenically exposed to DMH by 63.8% (Metallothionein), it was still similar to 51% higher than for animals fed a regular diet. Staining colon samples with an anti-gamma H2A.X antibody confirmed these findings. We suggest that tamarind has chemoprotective activity against the development of colon carcinogenesis, although a hypercholesterolemic diet might impair this protection. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Lipid peroxidation; Oxidative stress; Cholesterol; Tamarind; Hypercholesterolemia; Antioxidant potential